37.2k views
1 vote
Factor the polynomial x^2+(a+b)x+ab=(x+a)(x+b) using the pattern x^2+9x+8

User Yuby
by
5.2k points

2 Answers

3 votes

Answer:

hello : here is a general - method

x² + 9x + 8 = x²+(a+b)x+ab

you have the system : a + b = 9 .......(1)

ab = 8 ........(2)

solve this system : by (1) : b = 9 - a

subsct in (2) : a(9 - a ) = 8

9a - a² = 8

a² - 9a +8 = 0

calculate Δ = (-9)² - 4(1)(8) = 81 - 32 = 49 = 7²

a1 = ( 9-7)/2 = 2/2 =1 a2 = (9+7)/2 = 16/2 = 8

if : a = 1 b = 9-1 = 8 if : a = 8 b = 9-8 = 1

factor the polynomial x²+9x+8 = (x+1)(x+8)


User Doc
by
5.6k points
1 vote

Answer:(x+a)(x+b)

Hope this helps you.

Explanation:


Factor the polynomial x^2+(a+b)x+ab=(x+a)(x+b) using the pattern x^2+9x+8-example-1
User Ludwig Schulze
by
6.1k points